Persepsi Mahasiswa Hukum Keluarga Islam Universitas Nahdaltul Ulama Blitar terkait Perkawinan Anak di Blitar - Yaoma tartibi; Arum Ayu Lestari; Hengki Hendra Pradana (SINDA: Comprehensive Journal of Islamic Social Studies, 2022)
Child marriages from year to year have increased, of course, data relating to domestic violence, poverty, psychiatric disorders have also increased. This research has a goal of being able to find out the causes of increased child marriage in Blitar. This research uses field research and library research. The results of this study are known that the factors that cause child marriage are caused by cultural factors, internal (Family), and also economic factors.